PENGEMBANGAN MARKETING KNOWLEDGE DITENGAH PERBEDAAN PERSPEKTIF AKADEMISI-PRAKTISI - Amin Wibowo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
Knowledge is created and learned by academicians for the purpose of further theory development. Academician’role in disseminating knowldege is very important. To reach a convergent understanding both theory and practice, it’s a need of flexibility between methodology and sources of data so that it stimulates actionable insight.One of the problems between theory and practice differencesis customers focus.For practicians customer focus raised three foundamentals questions: can the knowledge phylosophy reduce cost?. Can the knowledge phylosophy increse sales?, and can the knowledge phylosophy increase the profit?. This paper discuss the development of marketing knowledge based on the marketing practice to bridge the gap between academicians and practicians. Issues being discussed in this paper are the meaning of marketing knowledge from practician perspective, the theory of marketing in practician’s world, actionable research as the bridge of knowledge development, and the difference perspective between academician and parctician.